THE DEFENSE FUND AND PUBLIC INITIATIVES IN THE NORTH OSSETIAN ASSR DURING THE GREAT PATRIOTIC WAR - Hubulova, Svetlana Alekseevna; Hablieva, Larisa Cermenovna; Kuliev, Farman Muruvvat ogly; Hubulova, Eda Vladimirovna (History, Archeology and Ethnography of the Caucasus, 2026)
This article examines a critical aspect of the history of the Great Patriotic War: the interaction between Party-Soviet structures and the public in providing comprehensive support to the Red Army, specifically within the North Ossetian ASSR. A key issue requiring modern re-evaluation is the scope of patriotic initiatives aimed at supporting Red Army soldiers. These included monetary donations, the collection of gifts and warm clothing for front-line troops, initiatives to fund the construction of tank columns and air squadrons, participation in war loans and lotteries, and voluntary labor shifts (voskresniks). The study identifies a range of difficulties and systemic problems encountered during these fundraising efforts. An analysis of archival materials from the Republic of North Ossetia-Alania suggests that these patriotic initiatives – implemented under the leadership and organizational guidance of Party and Soviet bodies – were vital to strengthening the country's national defense. Drawing on these archival sources, the authors evaluate the measures taken to provide multifaceted aid to the Red Army and highlight the historical experience of regional authorities in managing financial and material contributions. The research concludes that public initiatives in North Ossetia played a significant role in supporting the front, serving as a testament to the heroism and self-sacrifice of the Ossetian people.
Keywords: Defense Fund; the Great Patriotic War; autonomy of the North Caucasus; material and financial assistance to the Red Army; patriotic initiatives